2021
DOI: 10.1080/14786419.2021.2005049
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiglycation and antioxidant properties of Eugenia pyriformis leaves and fruits

Abstract: Eight phenolic compounds were isolated from Eugenia pyriformis leaves fraction by semipreparative HPLC and characterized by Nuclear Magnetic Resonance (NMR) and mass spectrometry (ESI-MS). Five compounds were isolated and identified for the first time in E. pyriformis species, while this is the first report of the accumulation of isoquercitrin, quercitrin, and the aglycone quercetin in its leaves. E. pyriformis leaves and fruits extracts, as well as the compounds isolated from the leaves most active fraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Phytochemical studies of the hydroalcoholic extracts of E. pyriformis showed the presence of alkaloids, flavonoids, tannins, and saponins in the leaf, but only the latter two classes were found in the stems [17]. Flavonoids were seen in leaves of E. pyriformis, such as myricitrin, isoquercitrin, hyperoside, quercitrin, myricetin-3-O-(2''-Ogalloyl)-α-L-rhamnoside, myricetin-3-O-(4''-O-galloyl)-α-L-rhamnoside and the aglycone quercetin [38]. Phenolic acids and flavonoids were detected abundantly in the fruit of E. pyriformis, predominantly comprising gallic acid, myricetin and quercetin [19,39].…”
Section: Phytochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemical studies of the hydroalcoholic extracts of E. pyriformis showed the presence of alkaloids, flavonoids, tannins, and saponins in the leaf, but only the latter two classes were found in the stems [17]. Flavonoids were seen in leaves of E. pyriformis, such as myricitrin, isoquercitrin, hyperoside, quercitrin, myricetin-3-O-(2''-Ogalloyl)-α-L-rhamnoside, myricetin-3-O-(4''-O-galloyl)-α-L-rhamnoside and the aglycone quercetin [38]. Phenolic acids and flavonoids were detected abundantly in the fruit of E. pyriformis, predominantly comprising gallic acid, myricetin and quercetin [19,39].…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…Studies regarding the antioxidant activity of the crude ethanolic extract and fractions of the leaf and stem of E. brasiliensis, E. beaurepaireana and E. umbelliflora using the DPPH test, potential reducer and inhibitor of lipid peroxidation showed that the first two species had higher antioxidant activity than E. umbelliflora in the crude extract and fractions of the leaf and stem, but a higher activity was observed in the leaf fractions, which contains phenolic compounds [10]. Ethanol: water (70:30 v/v) and ethyl acetate (EtOAc) extracts of the leaves and fruits of E. pyriformis showed antioxidant activity with (DPPH • ), 18.8 ± 0.4 and 8.4 ± 0.4 μg mL −1 and peroxyl radical (ROO • ), 6.4 ± 0.2 and 4.9 ± 0.4 μg mL −1 [38].…”
Section: Antioxidant Assaysmentioning
confidence: 99%
“…[1] Currently, natural compounds are widely recognized for their role as valuable sources of therapeutic agents, showcasing substantial antioxidant and anti-glycation properties. [2][3][4] These characteristics are commonly found in botanical sources, where antioxidants play a critical role in mitigating damage caused by reactive oxygen species through essential biochemical pathways. Cancer is a genetic disorder wherein dysfunctional cells divide nonstop and speedily spread to other organs of the body and is continuing to occur among populations of countries all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…We hereby present the separation, purification, and identification of the secondary metabolites obtained from the leaves of this plant. The secondary metabolites found in the study consist of a newly oxidized heptene, specifically 7-benzoyloxy-4-hydroxy-1-ethoxy-2E,4Z-heptadiene-1,6-dione, namely siamheptene A (1), together with eight previously identified compounds (2)(3)(4)(5)(6)(7)(8)(9). The study focused on investigating the anti-cancer properties of a new compound against Hela and A549 cell lines, as well as its antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation